An assessor-blinded, randomized comparative trial of transcutaneous auricular vagus nerve stimulation (taVNS) combined with cranial electroacupuncture vs. citalopram for depression with chronic pain - Li, Shaoyuan; Zhang, Zixuan; Jiao, Yue; Jin, Guixing; Wu, Yue; Xu, Fengquan; Zhao, Yufeng; Jia, Hongxiao; Qin, Zongshi; Zhang, Zhangjin; Rong, Peijing (Frontiers in Psychiatry, 2022)
Background: Depression accompanying chronic pain (CP) is one of the most common comorbid psychiatric disorders. This study aimed to investigate the effectiveness of transcutaneous auricular vagus nerve stimulation (taVNS) combined with electroacupuncture at Baihui (GV20) and Yintang (GV29) acupoints compared with citalopram. Methods: Sixty patients with depression and pain comorbidity were enrolled in a prospective 8-week, single-blind, randomized controlled trial. Participants were randomly assigned to receive either taVNS combined with electroacupuncture treatment (taVNS: 8 weeks, 3 sessions per week; electroacupuncture: 8 weeks, twice per day, no drugs) or citalopram treatment (8 weeks, 40 mg/day). The primary outcome was Montgomery–Åsberg Depression Rating Scale (MADRS). The secondary endpoints were evaluated using the McGill Pain Questionnaire (SF-MPQ), self-reported 36-Item Short Form Survey (SF-36), Pittsburgh Sleep Quality Index (PSQI), Hamilton Depression Rating Scale (HAMD) and Hamilton Anxiety Scale (HAMA). Results: Both the taVNS combined with electroacupuncture and citalopram groups had significant reductions in depressive and pain symptoms, as indicated by the decrease in MARDS and SF-MPQ scores. Regarding the analgesic effect, the pain intensity score of the SF-MPQ showed a larger reduction with citalopram than with taVNS combined with electroacupuncture at 6 weeks (P=0.036). The reduction in the BP score of the SF-36 was higher at week 4 (P=0.000), with no significant difference observed at week 8 (P=0.1110). This result indicated that the pain intensity can be improved rapidly with citalopram compared with taVNS combined with electroacupuncture. Similarly, the comparison of PSQI scores at 4, 6, and 8 weeks indicates that there was no significant difference between groups, except in the use of sleeping medications. At week 6, higher medication use was found in the citalopram group than in the taVNS combined with electroacupuncture group (P=0.049). Conclusion: In summary, compared with citalopram, taVNS combined with electroacupuncture produces similar positive effects on depressive and pain symptoms in patients with depression and chronic pain, which last for at least 8 weeks.